2010
DOI: 10.3109/08923970903349281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topical application of Brazilian propolis on scratching behavior induced by compound 48/80 in mice

Abstract: From these results, it can be concluded that inhibition of scratching behavior induced by topical application occurred by both its local anesthetic and systemic action through inhibition of histamine release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…By contrast, chrysin and kaempferol were below detectable levels in Brazilian propolis, possibly explaining why Brazilian propolis showed weaker inhibitory effects on mast cell degranulation than Chinese propolis. Consistent with the finding reported by Nakamura et al (2010), a few other studies by the same group of researchers (Shinmei et al, 2004(Shinmei et al, , 2009(Shinmei et al, , 2010 have also demonstrated the inhibitory effects of Brazilian green propolis ethanol extract on histamine release in rat peritoneal mast cells induced with compound 48/80, a commonly used mast cell activator. The results of propolis in allergic diseases such as asthma, allergic rhinitis and atopic dermatitis in which mast cell degranulation plays a crucial role are further discussed in subsequent sections.…”
Section: Mast Cell Degranulationsupporting
confidence: 86%
See 3 more Smart Citations
“…By contrast, chrysin and kaempferol were below detectable levels in Brazilian propolis, possibly explaining why Brazilian propolis showed weaker inhibitory effects on mast cell degranulation than Chinese propolis. Consistent with the finding reported by Nakamura et al (2010), a few other studies by the same group of researchers (Shinmei et al, 2004(Shinmei et al, , 2009(Shinmei et al, , 2010 have also demonstrated the inhibitory effects of Brazilian green propolis ethanol extract on histamine release in rat peritoneal mast cells induced with compound 48/80, a commonly used mast cell activator. The results of propolis in allergic diseases such as asthma, allergic rhinitis and atopic dermatitis in which mast cell degranulation plays a crucial role are further discussed in subsequent sections.…”
Section: Mast Cell Degranulationsupporting
confidence: 86%
“…The inhibitory effects of propolis increased gradually when the treatment was continued daily for 4 weeks. Similar therapeutic effects of Brazilian green propolis for atopic dermatitis were demonstrated by another study by Shinmei et al (2010), which assessed the efficacy of topical propolis to relieve itch in compound 48/80-induced rats. Interestingly, Brazilian green propolis ethanol extract applied at a dose of 3 mg per site on skin 60 min before the inducer compound 48/80 was injected intradermally suppressed scratching behaviours.…”
Section: Atopic Dermatitissupporting
confidence: 69%
See 2 more Smart Citations
“…Ten percent propolis treatment (1 mg/kg, once a day) inhibited the production of IgE, representative Th-2 cytokines, chemokines MCP-1 and TGF-β1, allergenspecific IgE, which resulted in inhibition of AHR (airway hyper-responsiveness) and reduced collagen deposition and the influx of inflammatory cells into the lungs of BALB/c mice challenged with allergens such as Dermatophagoides farine and diesel exhaust particles. In an experimental study by Shinmei et al [87] , propolis was given to rats for itchy nose and sneezing. The authors reported that symptoms were improved through decreased histamine release and that the longterm effects were favourable.…”
Section: Immunomodulatory Effect Of Propolis and Its Components On Bamentioning
confidence: 99%